Creating a Healthy School Community? Consider Critical Elements of Educational Change. Issue 4 (4th May 2017) - Gleddie, Douglas L.; Robinson, Daniel B.
Abstract : In recent years, the concept of creating and sustaining healthy school communities (HSC) has increased in popularity and acceptance as a way to link health and education outcomes within school communities across the globe. With the dual goal of enhancing student learning and facilitating action for health through education, schools with integrated, holistic and strategic HSC approaches have become exemplars for many others. Nonetheless, the introduction of an initiative such as HSC generally necessitates a change of practice and vision within already-established school communities and contexts. To address the resistance that might occur in such a scenario, this article provides a commentary on, and practical applications for, three aspects of school change that ought to be closely considered when implementing the concept of HSC within educational jurisdictions — namely, the important role of professional development, leadership capacity building, and cultural change in school settings.